Characterization of natural polymers for cosmetic applications - Botha, Carlo B. (2015)
ENGLISH ABSTRACT: The characterization of the molar mass and the chemical composition distributions of hyaluronic acid (HA), a linear polysaccharide, is an important task for developing structure-property correlations and for the advancement of various industrial applications. Some of the current techniques to obtain these distributions exhibit problems related to the poor sample solubility of virgin and modified HA since chemical composition and molecular size separations are typically conducted in solution. Therefore, there is a need for characterization techniques enabling the analysis of virgin and modified hyaluronic acid that are accurate, robust and reproducible. In the first part of this work solubility studies were performed on unmodified HA as well as HA modified with acrylic moieties. The aim of this work was to obtain suitable solvent systems for both species that can be used for size and chemical composition analysis. The solubility tests provided useful insight into solvents applicable for the chromatographic fractionation of the HA samples. The results gave a guideline for which solvent system is the most suitable for dissolving all the HA’s, irrespective of their degree of modification (degree of substitution, DS). For a first overview, the HA’s were analysed by bulk methods such as proton nuclear magnetic resonance (1H-NMR) and Fourier transform infrared (FT-IR) spectroscopy. From the bulk analyses, the average degrees of substitution of the HA’s were quantitatively determined by 1H-NMR spectroscopy. FT-IR spectroscopy was shown to provide fast and reliable information on DS of chromatographic fractions and is, therefore, complementary to 1H-NMR. In the present work, different analytical approaches have been developed for the chemical composition and molar mass characterization of HA and its derivatives. The combination of size exclusion chromatography (SEC) and multi-angle laser light scattering (MALLS) detection provided accurate molar mass distributions. The chemical composition separation was conducted by gradient high performance liquid chromatography (HPLC). In further investigations, these fractionation techniques were hyphenated with an information-rich detector such as FT-IR to obtain information on the degree of acrylate substitution of HA as a function of either molar mass or chemical composition. The results of this research showed that carefully conducted solubility tests are an important prerequisite for developing accurate and robust fractionation techniques. For very polar polymers such as HA and its derivatives, solvent systems must be found that suppress aggregate formation and enable the macromolecules to adopt random coil conformations. To our knowledge, the first gradient HPLC separation of HA bearing acrylate functionalities was successfully achieved in this work. The hyphenation of gradient HPLC with FT-IR provided insight into the separation mechanism and the functional group distribution of these polymers.